The Role of Regional Programs in Providing Road Safety (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes issues of road safety and regulatory legal documents regulating road traffic rules, development of regional programs for road safety , as well as researches related to this field.